Spatial‐temporal analysis of zinc homeostasis reveals the response mechanisms to acute zinc deficiency in Sorghum bicolor. Issue 4 (5th August 2013) - Li, Yulong; Zhang, Yuan; Shi, Dongqing; Liu, Xiaojing; Qin, Jun; Ge, Qing; Xu, Longhua; Pan, Xiangliang; Li, Wei; Zhu, Yiyong; Xu, Jin
Summary: Zinc (Zn) is an essential micronutrient in plants. The activity of copper/zinc superoxide dismutase (CSD) and carbonic anhydrase (CA) correlate with differences in Zn efficiency in plants; therefore, it is reasonable to hypothesize the existence of a Zn economy model that saves Zn for these essential Zn proteins during Zn deficiency. However, up to this point, direct evidence for the idea that CSD and/or CA might be priorities for Zn delivery has been lacking. Here, we investigated the spatial‐temporal effects of acute Zn depletion and resupply by integrating physiological studies and molecular analyses using hydroponically grown Sorghum . The elevated expression of miR398 repressed CSD expression in roots, whereas the reduced expression of miR528 resulted in a relatively stable level of CSD expression in Sorghum leaves under Zn depletion. Spatial‐temporal analysis after Zn resupply to previously depleted plants revealed that the expression and activity of CA were the first to recover after Zn addition, whereas the recovery of the activities of CSD and alcohol dehydrogenase (ADH) was delayed, suggesting that CA receives priority in Zn delivery over CSD and ADH. Our results also indicate that microRNAs (miRNAs) are important regulators of the response of Zn deficiency in plants.